Occupancy of pramipexole (Sifrol) at cerebral dopamine D2/3 receptors in Parkinson's disease patients - Angela Deutschländer; Christian la Fougère; Kai Boetzel; Nathalie L. Albert; Franz-Josef Gildehaus; Peter Bartenstein; Guoming Xiong; Paul Cumming (NeuroImage: Clinical, 2016)
Whereas positron emission tomography (PET) with the antagonist ligand [18F]fallypride reveals the composite of dopamine D2 and D3 receptors in brain, treatment of Parkinson's disease (PD) patients with the D3-prefering agonist pramipexole should result in preferential occupancy in the nucleus accumbens, where the D3-subtype is most abundant. To test this prediction we obtained pairs of [18F]fallypride PET recordings in a group of nine PD patients, first in a condition of treatment as usual with pramipexole (ON-Sifrol; 3 × 0.7 mg p.d.), and again at a later date, after withholding pramipexole 48–72 h (OFF-Sifrol); in that condition the serum pramipexole concentration had declined by 90% and prolactin levels had increased four-fold, in conjunction with a small but significant worsening of PD motor symptoms. Exploratory comparison with historical control material showed 14% higher dopamine D2/3 availability in the more-affected putamen of patients OFF medication. On-Sifrol there was significant (p ˂ 0.01) occupancy at [18F]fallypride binding sites in globus pallidus (8%) thalamus (9%) and substantia nigra (19%), as well as marginally significant occupancy in frontal and temporal cortex of patients. Contrary to expectation, comparison of ON- and OFF-Sifrol results did not reveal any discernible occupancy in nucleus accumbens, or elsewhere in the extended striatum; present methods should be sensitive to a 10% change in dopamine D2/3 receptor availability in striatum; the significant findings elsewhere in the basal ganglia and in cerebral cortex are consistent with a predominance of D3 receptors in those structures, especially in substantia nigra, and imply that therapeutic effects of pramipexole may be obtained at sites outside the extended striatum.